Renal biomarkers of Rosemarinus officinalis L. on gentamicine induced acute kidney injury in adult male albino rats (Rattus norvegicus) - Waswa, Kennedy W.; Kori, Scolastica (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Gentamicin (GN) drug is a common choice for treating severe gram-negative bacteria infections especially in resource-limited settings where cost effective options are considered. However, its potential effect of causing acute kidney injury (AKI) has limited its wide use in clinical applications. R. officinalis (rosemary) is a traditional herb rich in antioxidants and anti-inflammatory properties. Conversely, renal biomarkers effect of Rosmarinus Officinalis (RO) on GN has not yet been elucidated. The main objective was to investigate the renal biomarkers and protective effect of R. officinalis against Gentamicin induced acute Kidney injury in adult Albino rats. Methods: 25 adult male Albino rats were equally divided into five groups (5 Albino rats per group). Control group received rat pellets plus water ad libitum, GN (100 mg/kg/bwt/i.p), low dose RO (RO 100 mg/kg/bwt/po+GN), Medium RO(150 mg/kg/bwt/po+GN), and high dose RO (200 mg/kg/bwt/po+GN) groups. GN was administered intraperitoneal, and RO orally for seven consecutive days. After completion of 24hours of the last drug administration, they were humanely sacrificed, serum biochemical analysis of renal biomarkers (creatinine and urea) was determined. Results: Gentamicin was able to induced acute kidney injury by increasing levels of creatinine and urea. However, with concurrent administration of high dose of RO, Serum creatinine and urea remained within the normal ranges. Conclusions: These findings showed that, Concurrent administration of a high dose of RO 200 mg/kg/bwt with Gentamicin protects kidneys against Gentamicin induced injuries.